Respecting the Flag from an Islamic Perspective and State Regulations in Indonesia - Farida Roihanati; Husna Maulida Hasanah; Dayntikha Arlinie Soza; Shofiya Muthmainna (al-Afkar, Journal For Islamic Studies, 2026)
This research examines the view that saluting the Indonesian flag, which does not follow Islamic law, constitutes shirk (associating others with God). Although flag salutation has symbolized national unity since 1945, some modernist and Islamist groups consider it shirk. Islamic views on flag salutation are divided: the permissive perspective treats it as nationalism and patriotism, not shirk, if it is not seen as worship; the critical view equates it to idolatry, which belongs solely to Allah; and the moderate stance allows it when intended as nationalism, emphasizing intent and context. Using a literature review, the study explores historical, legal, and religious aspects of flag salutation and its societal effects. Despite differing opinions among scholars, the Indonesian government enforces flag salutation under Law No. 24 of 2009. The study concludes that flag salutation, as a patriotic act, aligns with Islamic values, promoting unity and national integration.